Effect of water extract of bay laurel (Laurus nobilis L.) on non-alcoholic fatty liver disease (NAFLD) - Minhee Lee; Jeongjin Park; Dakyung Kim; Seong-Hoo Park; Jaeeun Jung; Woojin Jun; Jinhak Kim; Kwang-Soo Baek; Ok-Kyung Kim; Jeongmin Lee (Food & Nutrition Research)
Non-alcoholic fatty liver disease (NAFLD) involves lipid accumulation in liver without consumption of alcohol and affects many people worldwide. NAFLD is associated with metabolic syndrome disease such as obesity, insulin resistance, hyperlipidemia, and diabetes. However, there are no pharmacologic therapies for NAFLD. Recently, there are increasing reports that several natural plants can inhibit lipid accumulation in hepatocytes. Bay laurel (Laurus nobilis L.) leaves have been used in traditional medicine for rheumatism, stomach ache, emetic, skin rashes, and earaches. Our objective was to investigate the effect of bay laurel leaves water extract (BLW) on free fatty acid (FFA) treated hepatocyte and high fructose, high fat (HFHF) diet in a mouse model of NAFLD. In vitro, lipid accumulation increased only in the FFA treated group, while BLW reduced lipid accumulation to a level comparable to that only in the FFA treated group. Cellular antioxidants were increased in the BLW compared to the only FFA-treated group, but cellular MDA levels were decreased in the BLW compared to the only FFA treated group. Cellular lipid accumulation, inflammation, and apoptosis were reduced in the BLW compared to the only FFA treated group. In vivo, serum ALT, AST, and GGT levels in the BLW supplementation group were significantly decreased compared with the HFHF group. Hepatic TC, TG, and MDA levels were significantly decreased in the HFHF+100 and HFHF+200 groups compared to the HFHF group. The hepatic antioxidant activities in the BLW supplementation groups were significantly increased compared to the HFHF group. The expression of proteins related to hepatic inflammation and apoptosis was reduced in the BLW supplementation groups compared to the HFHF group. These results suggest that BLW could be potentially useful in the treatment of NAFLD due to its inhibitory effects on hepatic lipogenesis, hepatic inflammation, and hepatic apoptosis.